2015
DOI: 10.1021/jacs.5b07487
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Multidimensional Self-Assembly of Polyphenylene-Based “Rod–Coil” Graft Polymers

Abstract: We present a novel type of "rod-coil" graft copolymer containing a polyphenylene backbone linked with poly(ethylene oxide) (PEO) side chains. Such graft copolymers manifest unprecedented temperature-dependent one-dimensional (1D) and two-dimensional (2D) self-assembly in solution. At 20 °C, which is higher than the crystallization temperature (Tc) of the PEO chains, the achiral graft copolymers self-organize into nanoribbons that twist into ∼30 μm ultralong helices with controlled pitch depending on the grafti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 25 publications
1
72
0
Order By: Relevance
“…This question can be better discussed, if the occurrence of π–π interactions and the structures of consequential assemblies can be varied by the desolvation conditions. This research is rarely reported, because π–π interactions in many systems are complicated by other forces and not sensitive enough to solution conditions for the study …”
Section: Methodsmentioning
confidence: 99%
“…This question can be better discussed, if the occurrence of π–π interactions and the structures of consequential assemblies can be varied by the desolvation conditions. This research is rarely reported, because π–π interactions in many systems are complicated by other forces and not sensitive enough to solution conditions for the study …”
Section: Methodsmentioning
confidence: 99%
“…Introduction of pendant moieties onto conjugated polymers to form graft copolymers is an effective pathway to improve their solubility and tailor their optoelectronic properties, which also provides opportunities to study their self‐assembly behavior and physiochemical properties of their self‐assembled structures in solution . Very recently, our group synthesized a novel type of rod‐coil graft copolymers containing an expanded poly‐ para ‐phenylene backbone grafted with PEO side chains (Fig.…”
Section: Self‐assembly Of Amphiphilic Rod‐coil Graft Copolymersmentioning
confidence: 99%
“…Very recently, our group synthesized a novel type of rod‐coil graft copolymers containing an expanded poly‐ para ‐phenylene backbone grafted with PEO side chains (Fig. ) . Featuring a unique structure with a short average distance between neighboring PEO chains on the conjugated backbone, these graft copolymers exhibited temperature‐dependent 1D and 2D hierarchical self‐assembly behavior in THF/H 2 O solution above and below the crystallization temperature of the PEO chains, respectively.…”
Section: Self‐assembly Of Amphiphilic Rod‐coil Graft Copolymersmentioning
confidence: 99%
“…In addition, helical morphologies are of fundamental scientific interest because a better understanding of physical and chemical behaviors of helical structures can provide crucial clues to understanding biological systems. Nevertheless, the realization of helically patterned, synthetic multicompartmental microbuilding blocks have been limited to a small number of techniques, such as E‐beam lithography15 or block copolymer self‐assembly methods 16…”
Section: Introductionmentioning
confidence: 99%